Balloon-Assisted Coils Embolization for Ophthalmic Segment Aneurysms of the Internal Carotid Artery - Chaohui, Liang; Yu, Zhang Guang; Kai, Hou (Frontiers in Neurology, 2021)
Objective: To explore the role of balloon-assisted coils technique for ophthalmic segment aneurysms (OSAS). Methods: Clinical data of 30 patients with OSAS were reviewed between December 2017 and December 2018. OSAS were defined as arising from the internal carotid artery (ICA), reaching from the distal dural ring to the origin of the posterior communicating artery. OSAS were classified into four types based on the angiographic findings. The balloon-assisted coils technique was used for the embolization of aneurysms. The duration of balloon inflation cycles, as well as difficulty and complications during the embolization procedure, were recorded. The immediate angiographic results were evaluated according to the Raymond scale. Clinical results were evaluated based on the MRS score. Follow-ups were performed at 18 months post-embolization by DSA or MRA at our institution. Results: Thirty-two aneurysms in 30 patients were detected by digital subtraction angiography (DSA), which included 30 unruptured and two ruptured cases. The patients with ruptured aneurysms were grade II status according to the Hunt-Hess scale. Three cases were type A, nine cases were type B, 17 cases were type C, and three cases were type D. According to aneurysm size, there were 19 cases of small, 11 cases of medium, two cases of large aneurysm. Thirty-two aneurysms were successfully embolized in 30 patients by balloon-assisted coils technique. The ophthalmic artery could be protected by an engorged balloon in the procedure, especially for type A aneurysms. Considering that type D aneurysm arises from the side-wall of the artery and near to tortuous ICA siphon, the balloon catheter was inflated to stabilize the microcatheter allowing for overinflation when necessary. The average duration of balloon dilatation was 4 min, and the average time was 2.5 times. Raymond class was one in 28 aneurysms and two in four aneurysms according to the immediate post-embolization angiographic results. All the patients achieved good clinical effects, except for one patient who presented with brain ischemia resulting in dizziness and contralateral limb weakness for 10 h due to prolonged temporary clamping of the responsible ICA. The follow-up angiography results were satisfactory at 18 months post-embolization. Conclusion: OSAS endovascular treatment with balloon-assisted coils has different advantages in a different classification. The technique is safe, effective, and relatively inexpensive, especially for small and medium OSAS.